Effectiveness Analysis of Arrival-Departure Service in Sultan Hasanuddin International Airport Mandai South Sulawesi - Ramlawati, Ramlawati; Rahmiati, Rahmiati; Hasnawati, Hasnawati; Yusra, Andi Nurfadilah; Sari, Andi Nila Ratna (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
The Purpose of this study: (1) To analyze the effectiveness of air services suddenly departed at Sultan Hasanuddin International Airport Mandai South Sulawesi. (2) To determine the aircraft parking apron arriving and ready to be dispatched is still adequate. Methods of data analysis used in this study adapted to the characteristics of the runway at the Sultan Hasanuddin International Airport Mandai South Sulawesi, namely (1) Using the queuing model Single Channel Single Phase (SC-SP), (2) λ = arrival rate of the average air per hour, (3) μ = aircraft capable of being served on average per hour, (4) Lq = number of units in the queue, (5) Ls = number of units in the system, (6) Wq = wait time average, ( 7) Ws = the average waiting time in the system, (8) P = the intensity level of service facilities. From the analysis of the data, Sultan Hasanuddin International Airport using queuing model Single Channel Single Phase (SC-SP) and the queue discipline First Come First Served (FC-FS). Average number of planes coming in was the best 5 per hour and the average number of aircraft served are the best 6 per hour. The average number in the system is the best 5 per hour and the average number of aircraft in the queue are 4 aircraft per hour. Based on the queuing model analysis for the aircraft, it indicates that the effectiveness of air services at Hasanuddin International Airport has been satisfactory, and the apron capacity is adequate.